Distinctive denitrifying capabilities lead to differences in N2O production by denitrifying polyphosphate accumulating organisms and denitrifying glycogen accumulating organisms. (November 2016) - Ribera-Guardia, Anna; Marques, Ricardo; Arangio, Corrado; Carvalheira, Monica; Oehmen, Adrian; Pijuan, Maite
Graphical abstract: Highlights: Denitrification kinetics for a dPAO and a dGAO culture are studied separately. N2 O accumulation is higher in dGAOs than in dPAOs. Nitrite inhibits the nitrous oxide reduction in dGAOs but not in dPAOs. There is no electron competition in any of the cultures. Abstract: This study aims at investigating the denitrification kinetics in two separate enriched cultures of denitrifying polyphosphate accumulating organisms (dPAO) and denitrifying glycogen accumulating organisms (dGAO) and compare their N2 O accumulation potential under different conditions. Two sequencing batch reactors were inoculated to develop dPAO and dGAO enriched microbial communities separately. Seven batch tests with different combinations of electron acceptors (nitrate, nitrite and/or nitrous oxide) were carried out with the enriched biomass from both reactors. Results indicate that in almost all batch tests, N2 O accumulated for both cultures, however dPAOs showed a higher denitrification capacity compared to dGAOs due to their higher nitrogen oxides reduction rates. Additionally, the effect of the simultaneous presence of several electron acceptors in the reduction rates of the different nitrogen oxides was also assessed in dPAOs and dGAOs.